NCMP-04. INCIDENCE AND OUTCOMES OF BRAIN METASTASES IN PATIENTS WITH EXTRA-PULMONARY NEUROENDOCRINE NEOPLASMS. (9th November 2020) - Abedin Kapacee, Zainul; Dawod, Mohammed; Allison, Jennifer; Frizziero, Dr Melissa; Chakrabarty, Bipasha; Manoharan, Prakash; McBain, Catherine; Mansoor, Was; Lamarca, Angela; Hubner, Richard; Valle, Juan; McNamara, Mairead
Abstract: BACKGROUND: Brain metastases (BMs) incidence in patients with extra-pulmonary neuroendocrine neoplasms (EP-NENs) is unclear, with no available management recommendations. This study aimed to review the clinical presentation, management and survival outcomes of patients with EP-NENs and BMs at a European Centre of Excellence. METHODS: A retrospective single-centre analysis of consecutive patients with EP-NENs (Aug 2004-Feb 2020) was conducted. Median overall survival (OS)/survival from BMs diagnosis were estimated (Kaplan Meier). RESULTS: Of 786 patients, 15 (1.9%) had BMs, median age 61y (range 15–77); 8 (53%) male, primary NEN site: unknown 40%; oesophageal 13%; small bowel 13%; pancreas 13%; gastric 7%; cervix 7% and bladder 7%. Most patients with BMs had grade 3 (G3) NENs (11, 73%), 3 (20%) were G2 and 1 (7%)G1. Eight (53%) had poorly-differentiated NENs, 6 well-differentiated and 1 not recorded. Two (13%) patients had synchronous BMs at diagnosis, whilst 13 (87%) developed BMs metachronously. Median time to development of BMs after initial NEN diagnosis: 15.9 months (range 2.5–139.5). Five patients had a solitary BM, 4 had 2–9 lesions and 6 had >10 BMs. The most commonly affected sites were the cerebrum (13, 87%), cerebellum (6, 40%), leptomeninges (2, 13%) and orbit (1, 7%). The most common presenting symptoms were limb weakness, headache, confusion, visual disturbance (each n=3, 20%), seizures (2, 13%), word-finding difficulty (2, 13%) and facial weakness/ptosis (1, 7%). Median OS from initial NEN diagnosis was 23.6-months [95%-CI 15.2–31.3]; median time to death from BMs diagnosis was 3.0-months [95%-CI 0.0–8.3]. Treatment of BMs was surgery (n=3); radiotherapy (n=6); 5 had WBRT, one localised radiotherapy (orbit). Six (40%) had best supportive care. CONCLUSION: BMs in patients with EP-NENs are rare and predominantly in G3 NENs, with diverse intracranial distribution. Although uncommon, BMs from NENs behave aggressively and greater understanding is needed to improve therapeutic outcomes.